Happy Birthday 'AT Source ' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
AT Source' (formerly Vraagbaak) special issue containing updated versions of the ten best articles published since 1972